Delayed ventricular pacing failure and correlations between pacing thresholds, left ventricular ejection fraction, and QTc values in a male with Takotsubo cardiomyopathy. Issue 11 (20th November 2018) - Brunetti, Natale D.; D'Arienzo, Girolamo; Sai, Rafel; Pellegrino, Pier L.; Ziccardi, Luigi; Santoro, Francesco; Di Biase, Matteo
Abstract : Background: Transient pacing failure caused by transient increased pacing threshold has been reported in patients with transient left ventricular apical dysfunction (Takotsubo cardiomyopathy [TC]). Normal pacing thresholds usually recover after normalization of systolic dysfunction. Hypothesis: Pacing failure correlates with clinics of TC. Methods: We report the case of a 76‐year‐old man with a dual chamber pacemaker, admitted for acute chest pain and dyspnea and final diagnosis of TC. One month after index admission, the patient came back complaining again of chest pain. Unexpectedly, admission electrocardiogram showed ventricular pacing failure and an increased pacing threshold. In the following weeks, pacing threshold gradually recovered with left ventricular ejection fraction and QTc values. Results: Ventricular pacing threshold correlated directly to QTc values and inversely to left ventricular ejection fraction over time ( P  < 0.05). Conclusions: This is one of the first cases of delayed transient ventricular pacing failure in a male patient with transient left ventricular apical ballooning, in the presence of spared right ventricular function. Given the possibility of acute transient anomalies in myocardial impedance and pacing failure even in the subacute phase of TC several weeks after clinical onset of transient systolic dysfunction, pacing threshold should be carefully monitored in subjects with TC, both during the acute phase of the disease and in first months of follow‐up after discharge. Ventricular pacing threshold correlated directly to QTc values and inversely to left ventricular ejection fraction over time.